Studi Komparatif Obesitas dan Non-Obesitas Berdasarkan Asupan Junk Food di SMA Tarakanita Gading Serpong - Stanislas Kotska Marvel Mayello Teguh; Alexander Halim Santoso (Malahayati Nursing Journal, 2024)
ABSTRACT The prevalence of obesity among adolescents is increasing. One major factor is the consumption of junk food. The ease of serving, variety, better taste, and marketing make teenagers prefer to consume junk food rather than foods that contain healthy nutrition. The purpose of this study was to determine the comparison between obese and non-obese students on junk food consumption at Tarakanita Gading Serpong senior high school. This study is a cross-sectional study with a total of 162 students. Students were asked to fill out a questionnaire related to junk food consumption and take measurements of body weight and height. The results of these measurements were mapped onto the CDC growth chart to obtain their nutritional status. There was a significant mean difference between obese and non-obese students in terms of junk food consumption (p0.05). Students should be aware of the impact of junk food consumption on health through continuous education, provision of healthy canteens in schools, and increased sports activities. Keywords: Junk Food, Obesity, Body Mass Index, Senior High School  ABSTRAK Prevalensi obesitas di kalangan remaja semakin meningkat. Salah satu faktor yang berperan berperan besar adalah konsumsi junk food. Kemudahan dalam penyajian, variasi, rasa yang lebih enak rasa,  dan pemasarannya membuat remaja lebih memilih untuk mengonsumsi junk food daripada makanan yang mengandung gizi sehat. Tujuan dari penelitian ini adalah untuk mengetahui perbandingan antara siswa obesitas dan non obesitas terhadap konsumsi junk food di SMA Tarakanita Gading Serpong. Penelitian ini merupakan penelitian potong lintang dengan jumlah siswa 162 orang. Siswa diminta untuk mengisi kuesioner terkait konsumsi junk food  dan melakukan pengukuran berat badan dan tinggi badan. Hasil dari pengukuran tersebut dipetakan ke dalam grafik pertumbuhan dari CDC untuk didapatkan status gizinya. Terdapat perbedaan rerata yang signifikan antara siswa yang mengalami obesitas dan tidak mengalami obesitas berdasarkan konsumsi junk food (p0,05). Kesadaran akan dampak konsumsi junk food terhadap kesehatan harus lebih ditingkatkan di kalangan siswa melalui edukasi berkesinambungan, pengadaan kantin sehat di sekolah, serta peningkatan kegiatan olahraga. Kata Kunci: Junk Food, Obesitas, Indeks Masa Tubuh, SMA